Bacurú Drõa: Indigenous forest custody as an effective climate change mitigation option. A case study from Darién, Panama - Kunz, Matthias; Barrios, Hector; Dan, Michelle; Dogirama, Iran; Gennaretti, Fabio; Guillemette, Mathieu; Koller, Alexandra; Madsen, Chris; Lana, Gilberto; Ortega, Alexis; Ortega, Manuel; Paripari, Jose; et al. (Frontiers in Climate, 2022)
Efforts to naturally remove atmospheric CO2 demand that largely intact forests be maintained. Our inter-cultural research initiative tested the hypothesis that Indigenous custody of the land is compatible with the maintenance of intact forests. Here we combined traditional knowledge, phytolith analysis, remote sensing, and tree inventories to study old-growth forests in Panama's Darién. Phytoliths served to elucidate historical vegetation, remote sensing revealed the current and past Indigenous footprints while tree stature and identity characterised the forest. Until now there has been very little to no human impact within these forests and current Indigenous footprint is both small and stable. Large trees accounted for 13% of trees in the plots that we established. For over half of the species, the measured tree height was taller than previously published maximum heights, leading us to conclude that these forests are a truly exceptional ecological refugium. Noting that the local communities are not rewarded for their custody of these exceptional forests we call to revisit the Good Practice Guidance for Land Use Land Use Change and Forestry to include intact forest land. In the context of sub-optimal carbon finance options, we also propose matching as a methodology that could prove additionality of forest conservation initiatives in climate mitigation portfolios.